Pendidikan Anak Perspektif Psikologi - Nurliana Nurliana; Miftah Ulya (Al-Liqo: Jurnal Pendidikan Islam, 2021)
The success of children's education is the success of a nation. Teachers must understand the psychology of learning so that education can play a role and influence children. This research was descriptive in the form of library research which was formulated through deductive analysis. Research on children's education with a psychological perspective needs to be carried out to determine the acceptance of children to the environment (family, school, and surroundings) in providing valuable education for children in line with their psychological development, and they can undergo the learning process through a conducive environment.